Nubian ceremonial life studies in Islamic syncretism and cultural change - Kennedy John G; Kennedy, John G (Berkeley University of California Press, 1978)
Islam
Includes index
Bibliography: p. 245-250
8
Keywords: Nubians -- Egypt -- Religion